Primary Synovial Sarcoma of the Scrotum - Nourah Al-Oudah; Sara Alanazi; Sarah Saad Alotaibi; Nayef Alzahrani (Case Reports in Pathology)
The report outlines a case of synovial sarcoma in the scrotal region. A 36-year-old male presented with a scrotal swelling. The lesion was completely resected, whereas the histopathologic examination revealed a spindle cell tumor. The tumor stained positive for pancytokeratin, AE1/AE3, epithelial membrane antigen (EMA), TLE-1, CD99, and BCL-2. The cytogenetic testing showed a chromosomal translocation in the SS18 gene at 18q11.2, consistent with the diagnosis of primary synovial sarcoma. A year later, the patient developed liver, vertebrae, and lung metastasis, which was treated with systemic chemotherapy. Treatment failed to improve the hepatic lesion that was then resected, while the spine and lung lesions were followed by radiotherapy. The patient is now alive and subject to an outstanding follow-up.